Optimality conditions for interval valued optimization problems - Villanueva, Fabiola R.; de Oliveira, Valeriano A. [UNESP]; Costa, Tiago M. (Elsevier, 2022)
This work addresses constrained optimization problems in which the objective function is interval-valued while the inequality constraints functions are real-valued. Both necessary and sufficient optimality conditions are derived. They are given through the gH-gradient and the gH-directional derivative of the interval objective function. The necessary ones are of KKT-type. The sufficient conditions are of generalized convexity type. The developed theory is illustrated by means of some numerical examples.
Keywords: Generalized convexity; Interval optimization; Karush-Kuhn-Tucker-type conditions; Necessary optimality conditions; Sufficient optimality conditions